Relationship science informed clinically relevant behaviors in Functional Analytic Psychotherapy: The Awareness, Courage, and Love Model - Maitland, Daniel W. M.; Kanter, Jonathan W.; Manbeck, Katherine E.; Kuczynski, Adam M. (Perspectivas em Análise do Comportamento, 2022)
The use of idiographically defined target behaviors in Functional Analytic Psychotherapy (FAP) has limited participation in a reticulated model of treatment development. One way to address this limitation is to offer a standardized set of clinical targets for FAP. The current study details a method of identifying standardized treatment targets in FAP using the Awareness, Courage, and Love (ACL) model. The applicability of the model was assessed by evaluating the degree to which previously identified clinical targets in FAP research correspond with the proposed specific categories of the ACL model. There is an 83.67% fit between past idiographic targets and current standardized targets. We discuss how ACL may be clinically useful and encourage more integrative treatment development for FAP.